Tumor Budding Is Independently Predictive for Lymph Node Involvement in Early Gastric Cancer. (August 2015) - Gulluoglu, Mine; Yegen, Gulcin; Ozluk, Yasemin; Keskin, Metin; Dogan, Serap; Gundogdu, Gökçen; Onder, Semen; Balik, Emre
Background . The most important prognostic factor for early gastric cancer (EGC) is the lymph node status. It is important to predict early lesions without lymph node metastasis (LNM) before proceeding to radical surgery in locally excised lesions. Tumor budding is a feature known to be related to aggressive tumor behavior in several solid tumors. We aimed to assess the predictive value of tumor budding for LNM in pT1a and pT1b gastric cancer. Methods . We retrospectively investigated radical gastrectomy specimens for of 126 EGC patients and assess the possible relation between the clinicopathologic features, including age, gender, tumor location, tumor size, macroscopic tumor type, histologic differentiation, depth and width of submucosal invasion, lymphovascular invasion, and tumor budding with lymph node involvement. Results . Among the 126 EGCs, 38 were stages as pT1a and 88 as pT1b. LNM rate in pT1a tumors was 13% whereas it was 33% in pT1b tumors. Tumor budding was the only factor significantly and independently related to LNM in pT1a patients. Female gender and tumor budding were found to be independent risk factors in pT1b group. Other clinicopathologic features were not related to LNM. Conclusion . Based on these results, we suggest that budding is a promising parameter to assess for prediction of LNM in EGC removed by endoscopic surgery, and to decide on the appropriate surgical approach.